1980
DOI: 10.1136/bmj.281.6252.1395
|View full text |Cite
|
Sign up to set email alerts
|

Risks from cannulae used to maintain intravenous access.

Abstract: 0 96 mmol/l (2 9 mg/100 ml), alkaline phosphatase 150 IU/l, and urea 3 8 mmol/I (23 mg/lO0 ml). Serum immunoassayable parathyroid hormone *Significant difference (p < 0005; xI test). tNo significant difference. Significant difference (p<0005; Student's t test).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In both countries, nurses and physicians preferred the forearm as an insertion place but for different reasons. Contrary to this, Swedish studies (Lundgren et al 1993, 1995) showed that nurses mainly used the dorsum of the hand despite their stated intention; this has also been confirmed by MacFarlane et al (1980) and Maki & Band (1981). Some argued that the vein on the forearm gives a lower risk of infection when administering hypo‐ or hypertonic medication.…”
Section: Discussionmentioning
confidence: 89%
“…In both countries, nurses and physicians preferred the forearm as an insertion place but for different reasons. Contrary to this, Swedish studies (Lundgren et al 1993, 1995) showed that nurses mainly used the dorsum of the hand despite their stated intention; this has also been confirmed by MacFarlane et al (1980) and Maki & Band (1981). Some argued that the vein on the forearm gives a lower risk of infection when administering hypo‐ or hypertonic medication.…”
Section: Discussionmentioning
confidence: 89%
“…The disadvantages of the intravenous route are numerous. Thrombophlebitis often occurs, especially if plastic catheters are used (3). Cannula infection is common and may lead to fatal septicemia, and the possibility of embolism, whether by foreign particles or air, is always present (4, 5).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have, however, reported factors of importance in preventing complications that arise when PIVs are used. Examples of those factors are good technique ( Hessov, 1985; Mossberg, 1993), good hygiene (Maki et al ., 1983), a well‐fixed small cannula ( Mossberg, 1993), good location ( MacFarlane et al ., 1980 ) and avoidance of hypo‐ or hypertonic solutions ( MacFarlane et al ., 1981 ; Hamory, 1987).…”
Section: Introductionmentioning
confidence: 99%